Probiotics SOD inhibited food allergy via downregulation of STAT6-TIM4 signaling on DCs. (November 2018) - Yang, Bo; Luo, Yan; Liu, Zhigang; Yang, Pingchang; Gui, Yaoting
Highlights: Administration of a single strain of human probiotic bacteria, BB, suppressed OVA-induced food allergy in mice. BB acts protective effect on allergic mice via its antioxidative enzyme, SOD. BB could further reduce TIM4 expression by inhibiting transcription factor STAT6. Abstract: Bacterial probiotics are of increasing use against intestinal disorders such as food allergy. However, the detailed molecular mechanism underlying probiotics-mediated anti-allergic effect remains unknown. In the present study, we orally treated OVA-sensitized mice with Bifidobacterium infantis (BB) for two weeks. It was found that OVA specific-IgE and-IgG levels in serum were significantly decreased after BB administration. BB treatment also significantly reduced the release of IL-4, -5, -13 in splenocytes. Besides, after challenge with OVA, the occurrence of temperature drop and diarrhea was dramatically reduced in BB group. Moreover, the protective effect of BB on allergic mice was correlated with its antioxidative enzyme, superoxide dismutase (SOD). The antioxidative effect of BB on Dendritic cells (DCs0 was further demonstrated to be mediated by cAMP/PKA signaling. We also found that the mRNA and protein expression levels of TIM4 were attenuated in BB group. Finally, ChIP-qPCR assay studies indicate that BB reduced the binding of STAT6 to its response elements in the TIM4 promoter. In conclusion, orally administration of BB protected allergic mice via attenuation of oxidative stress, which further reduced TIM4 expression by inhibiting its transcription factor STAT6.